RELATIONSHIP BETWEEN PHYSICAL ACTIVITY, ACADEMIC PERFORMANCE, AND BEHAVIOR IN ADOLESCENTS (Fiep Bulletin - online, 2025)
Introduction: In recent years, several studies have highlighted the importance of physical activity and sports in schools. These studies indicate that promoting movement and motor activities can significantly enhance students' cognitive functions, as well as positively impact their academic performance and behavior in the classroom. Objective: To compare the academic performance and behavior of students with different levels of physical activity in a full-time school in Teresina, PI, and to investigate the relationship between activity level and academic achievement. Methods: The study involved 38 students from the 2nd year of high school, aged 15 to 17, and thirteen teachers of both genders. A descriptive and quantitative approach was used, employing school reports, the "Piers-Harris Children’s Self-Concept Scale," a questionnaire developed by the author, and the IPAQ for activity level classification. Results: No significant differences were observed between physical activity level and overall academic and behavioral improvement among students. However, a positive correlation was found between math performance and physical activity level. Teachers unanimously agreed on the crucial importance of physical activity for students' academic performance and behavior. Conclusion: Although physical activity level did not directly influence students' behavior, there was evidence of a positive relationship with academic performance in mathematics.
Keywords: Physical Activity; Academic Performance; Behavior; Self-Concept